EFISIENSI MODAL INTELEKTUAL DAN NILAI BUKU PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di BEI Tahun 2011-2020) - Sita Kusuma Nugrahaeni; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of intellectual capital performance on the book value of companies listed on the Indonesia Stock Exchange in 2016-2020. This study uses the dependent variable Economic Value Added (EVA) and Free Cash Flow (FCF), the independent variable Intellectual Capital. The population used in this study are companies listed on the Indonesia Stock Exchange in 2011-2020. By using purposive sampling in sample selection, 220 research samples were obtained for 5 consecutive years (2016-2020). Testing the hypothesis of this study using multiple regression analysis method. The findings of this study reveal that intellectual capital performance has a positive and significant effect on Economic Value Added (EVA) and intellectual capital performance has a positive and significant effect on Free Cash Flow (FCF).